Selection of Lactic Acid Bacteria (LAB) Antagonizing Vibrio parahaemolyticus: The Pathogen of Acute Hepatopancreatic Necrosis Disease (AHPND) in Whiteleg Shrimp (Penaeus vannamei) - Nguyen Thi Truc, Linh (Biology (Basel), 2019)
Acute hepatopancreatic necrosis disease (AHPND) has recently emerged as a serious disease of cultured shrimp. A total of 19 lactic acid bacteria (LAB) strains isolated from shrimp samples were characterized based on morphological characteristics, biochemical tests, sequencing analysis, and their ability to antagonize Vibrio parahaemolyticus, which causes AHPND in whiteleg shrimp. Results from the agar well diffusion method indicated that 3 out of 19 isolated LAB strains showed the highest antagonizing ability against AHPND V. parahaemolyticus strain with an inhibition zone diameter ranging from 18 to 20 mm. Experiments where shrimps were given feed supplemented with these LAB strains and challenged with AHPND strain showed high survival rates (approximately 80.0%), which were not significantly different as compared to those recorded in the negative control treatment (86.6%), but significantly different to those recorded in the positive control treatment (40.6%) after 16 days of the experiment. However, the histological images of shrimp hepatopancreas indicated that the infection rate significantly reduced from 60.0% to 11.1% in shrimps fed with LAB-supplemented feeds and challenged with AHPND V. parahaemolyticus strain as compared to those in the positive control treatment. A polymerase chain reaction (PCR) and 16S rRNA gene sequencing confirmed the identification of LAB strain. These results can be applied in further experiments to investigate the ability of L. plantarum in preventing AHPND in intensively cultured whiteleg shrimp.